(untitled) (CIPEEX, 2023)
The objective of this study was to determine, through a systematic review of clinical trials, the acute effects of resistance exercise on affect in healthy young adults. Only articles published in English or Portuguese, with a sample of healthy young adults and that collected some acute affective variable related to resistance exercise, were selected. The criteria proposed by the PRISMA and PICOS approaches were used for the development of the review. 11 studies involving 606 young people (67.9% men) covered this review. Compared to the no-exercise control, resistance exercise with an intensity of 70-80% 1RM, 2-4 sets of 10 repetitions, and a recovery interval of 120-240 seconds between sets showed a better affective response. On the other hand, low and moderate intensities (40-70% 1RM), 3 sets of 5-20 repetitions, and a recovery interval of 30-90 seconds were more efficient in improving affective state compared to high intensities (80-100% 1RM), 3 sets of 4-10 repetitions, and a recovery interval of 90-150 seconds. Resistance exercise acutely improves affect in healthy young individuals, but the affective response depends on the type of exercise protocol used and other variables, such as the level of affect and the timing of post-exercise measurement. The available studies do not allow for the establishment of a dose-response relationship between resistance exercise and affect.